ELIMINASI LOGAM BERAT KADMIUM DALAM AIR LIMBAH MENGGUNAKAN TANAMAN AIR - Tuti Suryati (Jurnal Teknologi Lingkungan, 2003)
Aquatic plants (Eichornia crassipes, Pistia stratiotes and Salvinia cucullata)were grown in a nutrient solution in the presence of Cd ion (0,2 mg/L). Analysiswere performed to established whether there was a removal of Cd in solutionand there was accumulation of Cd in the roots and shoots of the plants.Analysis of Cd concentrations in water was performed everyday and at the endof the experiment the shoot and root of the plants was harvested. The resultsshowed that Cd concentrations in all solutions declined until tenth day.Eichornia crassipes could remove Cd in solution completely by six days. WhilePistia stratiotes and Salvinia cucullata of Cd removal rate were 93,5 % and 77,4%, respectively. Root to shoot concentration ratio of Cd was 36 for Eichorniacrassipes and 10 for Pistia stratiotes.